2016
DOI: 10.1139/cjpp-2015-0336
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of vildagliptin in chronic experimental cyclosporine A-induced hepatotoxicity

Abstract: The study examined the effect of dipeptidyl peptidase-4 (DPP-4) inhibitor, vildagliptin in cyclosporine (CsA)-induced hepatotoxicity. Rats were divided into 4 groups treated for 28 days: control (vehicle), vildagliptin (10 mg/kg, orally), CsA( 20 mg/kg, SC) and CsA-vildagliptin group. Liver function was assessed by measuring serum levels of Aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma glutamyltransferase (γGT), lactate dehydrogenase (LDH), albumin, and histopathological changes of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
3
13
1
2
Order By: Relevance
“…In addition, Alessandro and coworkers reported that testosterone decreased ROS production by binding to cytoplasmic androgen receptor (AR) and promoting its translocation to the nucleus, resulting in enhanced extracellular matrix (ECM) production via the transcription-inducing complex c-FOS/c-JUN (Bertolo et al 2014). Moreover, previous studies demonstrated that both testosterone (Mancini et al 2008, Zhang et al 2013 and vildagliptin (Avila Dde et al 2013, El-Sherbeeny & Nader 2016 could decrease oxidative stress by increasing the antioxidative substance such as catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx). This hypothesis is supported by the findings in this study that HFO and NDO groups had increased cardiac mitochondrial ROS production and that both testosterone and vildagliptin effectively attenuated cardiac mitochondrial ROS levels and reduced mitochondrial dysfunction (Chinda et al 2014.…”
Section: :1mentioning
confidence: 99%
“…In addition, Alessandro and coworkers reported that testosterone decreased ROS production by binding to cytoplasmic androgen receptor (AR) and promoting its translocation to the nucleus, resulting in enhanced extracellular matrix (ECM) production via the transcription-inducing complex c-FOS/c-JUN (Bertolo et al 2014). Moreover, previous studies demonstrated that both testosterone (Mancini et al 2008, Zhang et al 2013 and vildagliptin (Avila Dde et al 2013, El-Sherbeeny & Nader 2016 could decrease oxidative stress by increasing the antioxidative substance such as catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx). This hypothesis is supported by the findings in this study that HFO and NDO groups had increased cardiac mitochondrial ROS production and that both testosterone and vildagliptin effectively attenuated cardiac mitochondrial ROS levels and reduced mitochondrial dysfunction (Chinda et al 2014.…”
Section: :1mentioning
confidence: 99%
“…The limitations of our study included: the use of a single dose of vildagliptin and this was based on the fact that this dose showed protective effect in previous studies [10,28,48]; and a group with vildagliptin alone had not been done as the safety of vildagliptin was reported in healthy subjects in both experimental and clinical studies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of GGT have been shown to be associated with subclinic inflammation [42], CVS and metabolic diseases [43] [44]. It has been shown that cyclosporine hepatotoxicity is less in vildagliptin-given rats and has a positive effect on serum GGT [45]. In a Japanese study of type 1 diabetes, the correlation between DPP-4 activity and serum GGT was noted.…”
Section: Ggtmentioning
confidence: 99%